Partnerships and material aspects of the first edition of Germain Bazin’s books on the Brazilian baroque - Uribarren, María Sabina (Anais do Museu Paulista: História e Cultura Material, 2022)
Germain Bazin, art historian and chief curator of paintings at the Louvre Museum (1950-1965), authored two reference works on Brazilian colonial baroque, first published between 1956 and 1963. For his books on Brazil – one about colonial architecture, the other about the sculptor Aleijadinho –, Bazin received support from the National Historic and Artistic Heritage Institute (Iphan) and of Assis Chateaubriand, owner of Diários Associados. Thisessay delves into the partnerships established between them, sometimes unusual, but always effective in publishing writings about the Brazilian baroque and other goals connected to the artistic and museological fields. Bazin’s intellectual production has contributed to endorse the identity constructed by Iphan at a national and international level, and introduced the Brazilian colonial art, especially that of Aleijadinho, into the universe of world masterpieces. The published works, masterfully publicized by the Diários Associados, brought Iphan’s narrative closer to everyday discussions. Finally, the achievement of his books suggests a vindication space for the author, since he was questioned, following release of his work on Aleijadinho, regarding the transparency of his professional action in France.